Ten-Year Experience of Epidemiological Trends and Clinical Patterns of Vulvar Tumors in a Regional Cancer Center in India - Paul, Diptajit; Soni, Abhishek; Chatterjee, Sumit S; Chanda, Abhirup; Kaushal, Vivek; Chauhan, Ashok (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Vulvar tumors are relatively uncommon female genitourinary malignancies, primarily affecting postmenopausal women. Incidence and patterns of vulvar tumors vary across nations, influenced by numerous factors. This retrospective study aimed to evaluate the epidemiological patterns and clinical profiles of vulvar tumors in a regional cancer center in India. Material and Methods: This retrospective study was conducted at a regional cancer center in India over a 10-year period. Data on demographic profiles and tumor characteristics of all vulvar tumor patients were collected from the record section and reviewed. These data were analyzed to understand the clinic-epidemiological trends of vulvar malignancy. Results: A total of 47 patients with biopsy-proven vulvar malignancy were identified. The mean age at presentation was 63.4 years. The majority of patients were from rural origins, postmenopausal, and multiparous. Pruritus was the most common presenting symptom. Histopathologically, squamous cell carcinoma constituted the majority of cases. The labia was the most frequent site of presentation. Bilateral involvement was observed in one-third of patients, and inguinal lymphadenopathy and extensive disease were present in five and four patients, respectively. Conclusion: This study, conducted at the sole referral cancer institute in the state, highlights the clinic-epidemiological trends of vulvar tumors in the region. Limited studies from different regions of India have published local patient data on vulvar tumors. A nationwide collaborative effort is necessary to understand the precise burden of this relatively rare malignancy, identify epidemiological trends and risk factors, and inform management strategies for these patients.